The Origins of Common Identity: Evidence from Alsace-Lorraine - Sirus Dehdari; Kai Gehring (Center for Economic Studies and ifo Institute (CESifo), 2018)
The quasi-exogenous division of the French regions Alsace and Lorraine after the Franco-Prussian War allows us to provide evidence about group identity formation within historically homogeneous regions. Using several measures of stated and revealed preferences spanning over half a century, we show that being exposed to occupation and repression for many decades caused a persistently stronger regional identity. The geographical RDD results are robust across all specifications. We document two mechanisms using data on regional newspapers and regionalist parties. The differences are strongest for the first two age cohorts after WWII and associated with preferences for more regional decision-making.
Keywords: D91; H70; N40; Z19; 330; group identity; regional identity; identity formation; persistence of preferences; homogenization policies; assimilation; Alsace-Lorraine